Diversidad de invertebrados bentónicos del Río de la Plata - César, Inés Irma (2000)
The Rio de la Plata river present along the south coastal fringe different invertebrate assemblages related with substrate type, size sediment grains and organic matter content into the bedsediments. Other important factors influencing the distribution of benthos community in this river are the salinity and suspended solids of the water and the proximity to the riverside which increases the diversity of the habitats. The purpose of this study is to describe the taxonomic composition and ecological characteristics of the meso and macrobenthos associated with the river bed from Delta del Paraná to Magdalena, in Buenos Aires province. The listed taxa are the result of the revised literature and original data obtained from periodical samplings since 1993 till 1998. The principal components of the zoobenthos in the studied area were the allochthonous molluscs Corbicula fluminea on sandy and muddy bottoms and Limnoperna fortunei on hard substrates of the riverside. The nematods and oligochaetes dominated sediments with high allochthonous organic matter content imported from urban effluents. Palaemonetes argentinus, Macrobrachium borelli, Claudicuma platensis, Sinelobus stanfordi, Basphaeroma rhonbofrontale and Trichodactylus panoplus were the more common crustaceans in non polluted areas.